A Path Model of Workplace Solidarity, Satisfaction, Burnout, and Motivation. (January 2019) - MacDonald, Patrick; Kelly, Stephanie; Christen, Scott
Communication dynamics within the business world dictate that the formality of interaction between supervisor and subordinate is determined by the supervisor. The present study investigates the influence of negotiated formality and closeness via supervisor-subordinate solidarity on subordinates' burnout, motivation, and job satisfaction. An online questionnaire was administered to subjects across various occupations and organizations in the United States. The data are consistent with a mediated model in which job satisfaction mediates the relationships between solidarity-motivation and solidarity-burnout. These results are novel in that, first, job satisfaction is identified as an input of motivation and burnout rather than outputs of a shared induction, And, second, the results place renewed emphasis on the role of supervisor communication in the workplace as subordinates are unable to initiate solidarity.